2000
DOI: 10.1104/pp.124.3.1203
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation of Water and Water-Plasticized Biomolecules in Relation to Cellular Water Organization, Cytoplasmic Viscosity, and Desiccation Tolerance in Recalcitrant Seed Tissues

Abstract: To understand the relationship between the organization of cellular water, molecular interactions, and desiccation tolerance, dielectric behaviors of water and water-plasticized biomolecules in red oak (Quercus rubra) seeds were studied during dehydration. The thermally stimulated current study showed three dielectric dispersions: (a) the relaxation of loosely-bound water and small polar groups, (b) the relaxation of tightly-bound water, carbohydrate chains, large polar groups of macromolecules, and (c) the "f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
(59 reference statements)
3
35
0
Order By: Relevance
“…The implications of intracellular water organization for desiccation tolerance were discussed. Cytoplasmic viscosity increased exponentially at a water content < 0.40 g/g dry weight, which was correlated with the great relaxation slowdown of water-plasticized biomacromolecules, supporting a role for viscosity in metabolic shutdown during dehydration [395].…”
Section: Seedsmentioning
confidence: 83%
See 1 more Smart Citation
“…The implications of intracellular water organization for desiccation tolerance were discussed. Cytoplasmic viscosity increased exponentially at a water content < 0.40 g/g dry weight, which was correlated with the great relaxation slowdown of water-plasticized biomacromolecules, supporting a role for viscosity in metabolic shutdown during dehydration [395].…”
Section: Seedsmentioning
confidence: 83%
“…Sun [395] studied red oak (Quercus rubra) seeds analysing the relationship between the organization of cellular water, molecular interactions, desiccation tolerance, dielectric behaviours of water and water-plasticized biomacromolecules in these seeds during dehydration. The TSDC study showed three dielectric bands: (a) the relaxation of loosely-bound water and small polar groups; (b) the relaxation of tightly-bound water, carbohydrate chains, and large polar groups of macromolecules; and (c) the "freezing in" of molecular mobility (glassy state) (Fig.…”
Section: Seedsmentioning
confidence: 99%
“…Changes in the bound water fraction are at least partially the result of modifications in the levels of hydrophilic molecules with high water-binding capacity. It was reported that the bound water that represents unfreezable water (Wolfe et al 2002) plays an important role in tolerance to different environmental stresses, such as freezing and drought (Rascio et al 1998;Sun 2000). Indeed, fruit stored at low temperature under adequate high CO 2 concentrations had a larger bound water fraction (Goñi et al 2011), in association with an increase of inulin series fructans, which consist of linear β (2-1) linked fructose residues with a terminal glucose residue (Blanch et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1 and 5) is presumably associated with the saturation of all primary hydration sites. No consistent differences in the water sorption characteristics has been found between recalcitrant and orthodox seed tissues (Sun, 2000). Contrary to experimental data realized on viable seeds, Krishnan et al (2004aKrishnan et al ( , 2004c established that germinating and non-germinating seeds contained three types of water (bound, bulk and free water) in phase I of hydration.…”
Section: Germination As the Double Phase Shifting Of Watermentioning
confidence: 75%
“…From this point, seed viability could be maintained during long periods owing to their glass structure, which was defined by Buitink & Leprince (2004) as a thermodynamically unstable state, with high viscosity (enabled by low tissue moisture and low temperature), so as the viscosity is so high that diffusional movement is effectively prevented for time periods or practical utility. Sun (2000); Walters (2007); Buitink & Leprince (2008) ascertained that glass stability is not upheld per se, it is based on groups of different biomolecules, linked by hydrogen bonds with water molecules. Bryant et al (2001) and Benson (2008) suggested that the formation of a glassy matrix (i.e., vitrification) in could represent a strategy for desiccation tolerance and storage stability, in general.…”
Section: The Thermodynamics Of Seed and The Maintenance Of Seed Viabimentioning
confidence: 99%